1984
DOI: 10.1111/j.1365-2125.1984.tb05000.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of lignocaine and bupivacaine from the respiratory tract during fibreoptic bronchoscopy.

Abstract: Absorption of lignocaine and bupivacaine from the upper and lower respiratory tract was studied in patients undergoing fibreoptic bronchoscopy. No significant differences were found between the drugs and between the routes of administration in terms of the time taken to achieve maximum plasma concentrations. The relative availability of lignocaine was greater following administration via the upper respiratory tract, but bupivacaine availability did not differ. The apparent clearance of lignocaine was not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
1
4
2
Order By: Relevance
“…Although no previous data exist on the extent of systemic absorption of bupivacaine when used for posttonsillectomy pain management, there are some insights regarding its application within the oral cavity and other parts of the respiratory tract. In an assessment of bupivacaine absorption during fiberoptic bronchoscopy, the average peak concentrations were 271 and 273 ng/mL after application via the upper and lower respiratory tract, respectively 17 . Another investigation, focusing on the absorption of bupivacaine after oropharyngeal spray application in dosages between 20 and 80 mg 18 revealed that even the 20 mg dose yielded a concentration around 150 ng/mL, that is, higher than our findings.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Although no previous data exist on the extent of systemic absorption of bupivacaine when used for posttonsillectomy pain management, there are some insights regarding its application within the oral cavity and other parts of the respiratory tract. In an assessment of bupivacaine absorption during fiberoptic bronchoscopy, the average peak concentrations were 271 and 273 ng/mL after application via the upper and lower respiratory tract, respectively 17 . Another investigation, focusing on the absorption of bupivacaine after oropharyngeal spray application in dosages between 20 and 80 mg 18 revealed that even the 20 mg dose yielded a concentration around 150 ng/mL, that is, higher than our findings.…”
Section: Discussioncontrasting
confidence: 75%
“…In our study, peak concentration appeared, on average, 11 min postdrug application, which is faster than the 30-60 min reported in the aforementioned studies. [17][18][19] This suggests that our 4-min swab application of bupivacaine might have a reduced depot effect postremoval. Obviously, different formulations and application methods could lead to variations in absorption and concentration timelines.…”
Section: Mean ± Sd Min-maxmentioning
confidence: 99%
“…[6][7][8][9][10] Several clinical trials have examined lidocaine blood concentrations after topical anesthesia for bronchoscopy, finding nontoxic concentrations in all study subjects. [11][12][13][14][15][16] Other clinical trials, however, reported concentrations in the toxic range after similar application, suggesting a potential for t o~i c i t y .~~-~~ A decrease in lidocaine clearance was reported in elderly subjects. *' As a result, older patients undergoing bronchoscopy may be at greater risk for the development of elevated drug concentrations and signs and symptoms of toxicity after topical anesthesia.…”
mentioning
confidence: 99%
“…Aerosolized local anaesthetics are rapidly absorbed from the airways to yield substantial plasma concentrations [25,26]. The possibility exists, therefore, that the antitussive effect of lignocaine was due to an interaction of absorbed drug with peripheral or central nervous pathways in the cough reflex.…”
Section: Discussionmentioning
confidence: 99%